1986
DOI: 10.1021/bi00350a006
|View full text |Cite
|
Sign up to set email alerts
|

Deuterium NMR study of the interaction of .alpha.-tocopherol with a phospholipid model membrane

Abstract: The effects of 5, 10, and 20 mol % incorporation of alpha-tocopherol (vitamin E) on 50 wt % aqueous multilamellar dispersions of sn-2-substituted [2H31]palmitoylphosphatidylcholine (PC-d31), a saturated, deuterated phospholipid prepared from egg lysophosphatidylcholine, have been studied by deuterium nuclear magnetic resonance (2H NMR) and differential scanning calorimetry (DSC). Moment analysis of the 2H NMR spectra as a function of temperature and DSC heating curves demonstrate that the main gel to liquid-cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
31
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(40 citation statements)
references
References 31 publications
9
31
0
Order By: Relevance
“…The detergents and lipids are represented as sticks, the van der Waals surface are indicated as shadow and the hydrogen acceptors (oxygens) are in red. contrast to an increase in the acyl chain ordering by 17% [50]. Membrane ordering/disordering effects are generally observed at much higher concentrations than used to inhibit P-gp [51].…”
Section: The Influence Of Detergents On the Lateral Packing Density Omentioning
confidence: 99%
“…The detergents and lipids are represented as sticks, the van der Waals surface are indicated as shadow and the hydrogen acceptors (oxygens) are in red. contrast to an increase in the acyl chain ordering by 17% [50]. Membrane ordering/disordering effects are generally observed at much higher concentrations than used to inhibit P-gp [51].…”
Section: The Influence Of Detergents On the Lateral Packing Density Omentioning
confidence: 99%
“…Structurally, all four tocopherols (a-, b-, g-, and d-tocopherols) consist of a chromanol head group attached to a phytyl tail and differ only in the number and positions of methyl groups on the chromanol ring ( Figure 1). Tocopherols are amphipathic molecules, and in vitro studies using artificial membranes have shown that tocopherols form complexes with specific lipid constituents and physically stabilize membranes (Wassall et al, 1986;Stillwell et al, 1996;Wang and Quinn, 2000;Bradford et al, 2003). Tocopherols can efficiently quench singlet oxygen, scavenge various radicals, particularly lipid peroxy radicals, and thereby terminate lipid peroxidation chain reactions (Liebler and Burr, 1992;Bramley et al, 2000;Schneider, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…has concentrated on changes in the structure and permeability of the membrane. Usually mixed liposomes with phosphatidylcholine were used, and a variety of techniques were applied: differential scanning calorimetry (Cushley et al, 1979;Massey et al, 1982;Lai et al, 1985), I3C and 31P nuclear magnetic resonance (NMR)' (Cushley & Forrest, 1977), and recently 2 H N M R of deuteriated fatty acids in lipids (Wassall et al, 1986). It was found that a-tocopherol broadens and lowers slightly the temperature of the gel-liquid-crystal phase transition, increases ordering of lipids above the phase transition, and changes the permeability of model membranes.…”
mentioning
confidence: 99%